Isotopic Fission-yield Calculation of U-233, U-238 and Th-232 for Fast Energy Spectrum - Abdul Waris; Rizal Kurniadi; Yuda S. Perkasa; Suwoto Suwoto (Indonesian Journal of Physics, 2008)
An isotopic fission yield calculation method for fast energy spectrum of neutron has been proposed. This method was derived from a systematic of fission mass yield and a nuclei decay probability. The decay probability was calculated from the level density parameters that derived from a new potential function in combining with the shell correction. The potential function is a modified Wood-Saxon potential that we have called as an extended-Wood-Saxon potential. We have employed the data from RIPL-2 (Reference Input Parameter Library-2) in calculating the level density parameter. The calculation shows similar results compared to the isotopic mass yields of JENDL 3.2 for 233U and 232Th.